GAZE GAMES, AMONG HEGEMONIC VOICES AND SUBALTERNITIES. ANALYSIS OF THE STORY: “EL CLIS DE SOL” AND THE TRAVEL JOURNAL “SAN JOSÉ” - Brenes Montoya, Mónica (2015)
The paper proposes a critical analysis of the texts, “El clis de sol” from Manuel González Zeledón, Magón, and “San José” from the book Vacaciones en Costa Rica from Thomas Francis Meagher, translated by Ricardo Fernández Guardia. This analysis is performed based on elements such as popular culture, hegemony and subalternity. The paper is structured in four sections. The first section collects some initial considerations. The second section, “Literature as primary source: features, discussions and historical senses”, describes the main features of the primary sources utilized, the discussions around them and the historical sense that they contain. The third section, “Voices, spaces and popular cultures”, analyzes the hegemonic and subaltern voices which appear in the texts, as well as the spaces under tension that are evident in the texts. Finally, the four section, “Final Balance”, discusses the final considerations, guided by the opportunities to contemplate historical studies from these texts and other sources.